2020
DOI: 10.1038/s41598-020-63774-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and synchronous changes in metazoan body size during the Cambrian Explosion

Abstract: Many aspects of the drivers for, and evolutionary dynamics of, the cambrian explosion are poorly understood. Here we quantify high-resolution changes in species body size in major metazoan groups on the Siberian Platform during the early Cambrian (ca. 540-510 Million years ago (Ma)). Archaeocyath sponges, hyolith lophophorates, and helcionelloid mollusc species show dynamic and synchronous trends over million-year timescales, with peaks in body size during the latest tommotian/early Atbadanian and late Atdaban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 41 publications
1
36
0
Order By: Relevance
“…However, the variation of the linear body size was in interesting paces: the size of archaeocyath, hyolith, and helcionelloid mollusc species varied in a synchronous rhythm over million-year timescales, with peaks positively correlated with origination rate and total species diversity, which appear to be a consequence of external drivers. The response of brachiopods is quite different, calcitic shells showing a general increase in body size while phosphatic shells decreasing in size through time (Zhuravlev and Wood 2020).…”
Section: Increase Of Body Sizementioning
confidence: 97%
See 1 more Smart Citation
“…However, the variation of the linear body size was in interesting paces: the size of archaeocyath, hyolith, and helcionelloid mollusc species varied in a synchronous rhythm over million-year timescales, with peaks positively correlated with origination rate and total species diversity, which appear to be a consequence of external drivers. The response of brachiopods is quite different, calcitic shells showing a general increase in body size while phosphatic shells decreasing in size through time (Zhuravlev and Wood 2020).…”
Section: Increase Of Body Sizementioning
confidence: 97%
“…The large size was reached before the Cambrian Explosion. A quantitative study of skeletal species from Siberia demonstrated marked changes in maximum linear body size dimensions but no unidirectional trend throughout the early Cambrian (Zhuravlev and Wood 2020). However, the variation of the linear body size was in interesting paces: the size of archaeocyath, hyolith, and helcionelloid mollusc species varied in a synchronous rhythm over million-year timescales, with peaks positively correlated with origination rate and total species diversity, which appear to be a consequence of external drivers.…”
Section: Increase Of Body Sizementioning
confidence: 99%
“…It has been observed that hypercalcified forms such as archaeocyaths were especially adversely affected in the Stage 4 extinctions, possibly because anoxia impedes biomineralization as a result of reduced surface‐water carbonate supersaturation (Zhuravlev & Wood 2020). Calcite biomineralization may likewise have been detrimental to trilobites during anoxic pulses, and is possibly a factor in accounting for differences in survivorship compared to non‐biomineralized arthropods such as naraoiids, although it need be noted that other arthropods exhibit a high hypoxic sensitivity (John & Walker 2016; Zhang & Cui 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2017). Extinctions in Cambrian Series 2, for example, include the disappearance of the sponge group Archaeocyatha in the Cambrian Stage 4 Sinsk Event, and the loss of many lineages of trilobites, most notably of the Order Redlichiida, including the Olenellina towards the end of Series 2 and the Redlichiidae at the Series 2 – Miaolingian boundary (Zhuravlev & Wood 1996, 2018, 2020; Palmer 1998; Fagetter et al . 2017; Wood et al .…”
Section: Figurementioning
confidence: 99%
“…Following the putative extinction of the Ediacaran biota, animals showed significant increase in diversity and disparity over a relatively short interval of geological time during which origination rates greatly exceeded extinction rates [ 3 ]. The Cambrian Explosion led to defensive strategies against predation, including significant size increase [ 4 ]. However, the framework on which this novelty was built remains shrouded because Ediacaran antecedents are unknown, evidence of lineages spanning the Ediacaran–Cambrian transition and the Cambrian Explosion being scant.…”
Section: Introductionmentioning
confidence: 99%